Imperial metropolis : Los Angeles, Mexico, and the borderlands of American empire, 1865-1941 - Kim, Jessica M. (David J. Weber series in the new borderlands history., 2019)
"In this ... narrative of capitalist development and revolutionary response, Jessica Kim chronicles the imperial visions of the Los Angeles civic elites who fueled the city's phenomenal growth between the Civil War and World War II. Driven by the belief that an enterprising white-run city deserved to control a nonwhite periphery, wealthy Angelenos invested heavily in Mexican industries such as agriculture, petroleum, mining, and tourism, and transformed the countryside of northern Mexico, both to enrich themselves and to develop their home city as a new site of empire"--